Finite Element Analysis of Nylon Based 3D Printed Autonomous Underwater Vehicle Propeller - Khaleed,H.M.T. (2020)
Abstract The recent developments in the additive manufacturing to manufacture complex cost effective profiles is gaining popularity to test the strength of developed products through finite element method (FEM). Finite element analysis (FEA) is a potent tool for mechanical analysis. The combination of 3D printing and FEA is opening new opportunities to go further in the complexity of the product geometry. The autonomous underwater vehicle (AUV) propeller blade has a complex profile with multi-directional gradient and twist, which requires a multi-stage operation to manufacture, including the hubs. The AUV propeller is required to withstand the applied load and generate the required thrust to move AUV at the desired speed. The current study explores the performance of AUV propeller prepared by additive synthesis using Nylon 6 material. The design of the propeller blade was developed using SOLID WORKS and integrated to the CUBPRO (DUO) to obtain the required 3D printing parameters. A comparative investigation is made for Nylon material within the dimensional conformance with the 3D printed propeller blade. The stress-strain analysis of the Nylon AUV propeller is carried with the FEM. The analysis of error and the stress show that the Nylon material meets the performance criteria for AUV propeller.